2006
DOI: 10.1080/01443610500508220
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing gestational age at antenatal booking at the University College Hospital, Ibadan, Nigeria

Abstract: In order to achieve the aim of improved outcome of pregnancy for mother and fetus, early booking (first antenatal visit), prior to 14 weeks' gestation is usually recommended. A survey of information on personal data, index pregnancy, reasons for booking at a particular gestational age, past obstetric history and medical history of 205 pregnant women attending the antenatal booking clinic at the University College Hospital, Ibadan, Nigeria was carried out using a structured questionnaire. The mean gestational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
44
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 2 publications
22
44
3
Order By: Relevance
“…This finding is similar with the study conducted in Nigeria which suggests that pregnant women who were advised by physicians were booked timely (14). This suggested that proper information and advice on pattern of ANC utilization from service providers are important to book timely.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is similar with the study conducted in Nigeria which suggests that pregnant women who were advised by physicians were booked timely (14). This suggested that proper information and advice on pattern of ANC utilization from service providers are important to book timely.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is quite in line with the study done in South Africa which stated that unintended pregnancy is a factor for delays in seeking ANC (14). It is believed that, wanted pregnancies are more cared by the women and other significant individuals, which enables the women to book timely for ANC.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is lower than the mean gestational age at booking in Ibadan, Nigeria, Sagamu, Nigeria and Addis Ababa, Ethiopia. 8,11,16 However, most studies show a consistent high figure for late booking. 8,11 In Ethiopia, it was demonstrated that physical and financial accessibility was not enough to ensure proper utilisation of available health services; socio-cultural factors were also important in affecting utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 This is critical to early identification and management of underlying medical or obstetrics conditions that may affect the outcome of pregnancy eg. anaemia, malaria, Human Immunodeficiency Virus infection, and cervical incompetence.…”
Section: Introductionmentioning
confidence: 99%